Photolithography Fabricated Broadband Waveguide Grating Couplers With 1 dB Bandwidth Over 100 nm - Xuetong Zhou; Hon Ki Tsang (IEEE Photonics Journal)
In this paper, we propose and validate a new approach for increasing the optical bandwidth of waveguide grating couplers by using a center-symmetric grating structure. Our results demonstrate state-of-the-art performance in increasing the 1 dB optical bandwidth to 108 nm and experimentally validated coupling efficiency of −3.0 dB. The fabrication uses standard MPW fabrication service offered by commercial foundry with a minimum feature size above 181 nm. Such a flat wideband and high-efficiency performance is suitable for large-volume manufacturing and will enable the use of grating couplers in wideband applications such as wavelength division multiplexed communications, broadband applications of optical frequency combs and optical sensors.